2017
DOI: 10.1037/hea0000534
|View full text |Cite
|
Sign up to set email alerts
|

Is subjective social status a unique correlate of physical health? A meta-analysis.

Abstract: Objective Both social stratification (e.g., social rank) as well as economic resources (e.g., income) are thought to contribute to socioeconomic health disparities. It has been proposed that subjective socioeconomic status (an individual’s perception of his or her hierarchical rank) provides increased predictive utility for physical health over and above more traditional, well-researched socioeconomic constructs such as education, occupation, and income. Method PsychINFO and PubMed databases were systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
190
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(210 citation statements)
references
References 72 publications
14
190
3
3
Order By: Relevance
“…The Chinese version of this measure has been indicated to be reliable and valid (Kong et al, ; Wang et al, ). Previous studies have shown a close association between subjective SES and physical and psychological health (Adler et al, ; Cundiff & Matthews, ).…”
Section: Methodsmentioning
confidence: 89%
“…The Chinese version of this measure has been indicated to be reliable and valid (Kong et al, ; Wang et al, ). Previous studies have shown a close association between subjective SES and physical and psychological health (Adler et al, ; Cundiff & Matthews, ).…”
Section: Methodsmentioning
confidence: 89%
“…The traditional indicators used in most of the literature fail to fully capture the relationship between SES, stress, and health outcomes (Cundiff & Matthews, 2017;Saegert et al, 2007;U.S. Department of Health and Human Services, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has considered the notion of subjective socio‐economic status – a personal sense of their place in society and also referred to as socio‐economic position or subjective social status – as being a more robust measure of socio‐economic status. Significantly, an established evidence base and recent meta‐analysis now support that this may be a more robust measure than crude objective measures of socio‐economic status by measuring its association with health (Cundiff & Matthews, ). Nevertheless, what we know about subjective socio‐economic status and health is largely based upon empirical studies concerning the general population and therefore this scoping review set out to address our research question concerning its relationship with health in adults with intellectual disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%